Handwashing sinks as the source of transmission of ST16 carbapenem-resistant Klebsiella pneumoniae, an international high-risk clone, in an intensive care unit. Issue 4 (April 2020) - Feng, Y.; Wei, L.; Zhu, S.; Qiao, F.; Zhang, X.; Kang, Y.; Cai, L.; Kang, M.; McNally, A.; Zong, Z.
SUMMARY: Carbapenem-resistant Klebsiella pneumoniae (CRKP) isolates (carrying the carbapenemase gene bla NDM-5 ) of sequence type 16 caused hospital-acquired bloodstream infection or gut colonization in two patients in an intensive care unit (ICU). It was hypothesized that handwashing sinks were the source, and all handwashing sinks in the ICU were sampled. Whole-genome sequencing and analysis revealed that one sink was the source of CRKP colonization/infection in both patients, instead of direct transmission of a common clone between the patients. This study highlights handwashing sinks as an important source of multi-drug-resistant organisms. Sink management, including prohibition of disposal of body fluids and daily disinfection with chlorine, curbed the transmission.